2020
DOI: 10.1029/2019ea000898
|View full text |Cite
|
Sign up to set email alerts
|

Performance of GNSS Global Ionospheric Modeling Augmented by LEO Constellation

Abstract: The Low-Earth-Orbiting (LEO) satellite has a fast motion and thus contributes to rapid changes in satellite geometric distribution, which can effectively mitigate multipath effects and offer more available observations. Recently, some studies have investigated LEO-augmented Global Navigation Satellite System (GNSS) positioning and navigation. However, the study of LEO-augmented global ionospheric modeling was not yet available. In this paper, we present the performance and accuracy of global ionospheric model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The detailed processing strategies of the constellation simulation and the ionospheric observation simulation have been introduced by Ren et al. (2020b). In this study, the ground‐based STEC observations of LEO and GNSS satellites are simulated by using the IRI‐2016 model, and the LEO satellite constellation is designed to consist of 192 polar‐orbiting satellites.…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed processing strategies of the constellation simulation and the ionospheric observation simulation have been introduced by Ren et al. (2020b). In this study, the ground‐based STEC observations of LEO and GNSS satellites are simulated by using the IRI‐2016 model, and the LEO satellite constellation is designed to consist of 192 polar‐orbiting satellites.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Due to the sparse and unevenly distributed GNSS‐tracking stations worldwide, however, conventional GIMs can only achieve a lower accuracy with a mean precision of 2–8 total electron content unit (TECU), especially in ocean areas (Chen et al., 2017; Hernández‐Pajares et al., 2017; Ren et al., 2020a, 2020b; Yuan and Ou, 2002). As a result, typical multisource data such as satellite altimetry, radio occultation from LEO satellites and Doppler Orbitography, and Radio‐positioning Integrated by Satellite instrument (DORIS) are integrated into GNSS data providing an increase of VTEC accuracy (Alizadeh et al., 2011; Chen et al., 2014; Dettmering et al., 2011; Hernández‐Pajares et al., 2020; Ren et al., 2020b, 2021; Todorova et al., 2008; Yao et al., 2018). The results showed that the accuracy of GIMs has been improved to make up the deficiencies of the existing GIMs by adding space‐based data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once all the constellations are completed, the number of available LEO satellites would be in the tens of thousands [20]. Some of these LEO constellations can provide navigation augmentation services, which can contribute to precision point position (PPP) ambiguity solving, shorten convergence time [21,22], and improve the accuracy of the ionospheric model [23,24]. Compared with GNSS, LEO satellites have some of the following characteristics: lower orbits, stronger signals, less interference, longer trajectories across the sky in the same time, and faster geometry changes.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing number of Low Earth orbit (LEO) satellites in the near future, 3D ionosphere model will play an essential role in GNSS global ionospheric modeling augmented by LEO satellites (Ren et al, 2020). The increasing demand for ionospheric and space geodetic applications makes it of particular importance to assess the performance of the 3D ionospheric models from different aspects for the long‐term comprehensively.…”
Section: Introductionmentioning
confidence: 99%